IMPLEMENTATION OF TUNA DIRECT EXPORT POLICY IN NORTH SULAWESI PROVINCE - Jenuard M. Nelwan; Maria H. Pratiknjo; Novie Revli Pioh (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the implementation of the direct export policy of tuna in North Sulawesi province. This research uses a qualitative approach with descriptive methods. The information used in this study amounted to 5 people consisting of the head of the Marine and Fisheries Service of North Sulawesi Province, the fish processing unit and the fishing community. Data collection is done through observation, interviews and documentation. Sources of research data consist of primary data obtained directly through interviews and secondary data taken from books, journals, annual reports as well as literature and other supporting documents. This study focused on aspects of policy implementation consisting of size and objectives, inter-organizational communication resources, characteristics of implementing agencies, socio-political and economic conditions, and attitudes of implementers. Data analysis consists of data reduction, data presentation and conclusion or verification. The results of this study indicate that the implementation of the direct export policy for tuna is prepared to cut export costs which are too expensive due to the existence of an export route that is too long which will automatically affect the quality of the fish where the price of tuna will be affected by the quality of the fish that reaches the destination country, so that it can also affect the distribution process of tuna. In conclusion, the potential for tuna products in North Sulawesi has a significant impact and has a positive direction towards tuna exports between Indonesia and Japan in general and North Sulawesi to Japan or other countries in particular.